Sorption and Desorption of Tembotrione and its Metabolite AE 1417268 in Soils with Different Attributes - FARIA,A.T. (2019)
ABSTRACT: Tembotrione is registered in Brazil for maize and is used in large areas of the country in each harvest. In recent years, producers have reported carryover effects of this herbicide in succeeding crops to maize. This fact can be attributed to tembotrione recommendations without knowing their interactions with tropical soils colloids. In this study, using high-performance liquid chromatography, it was possible to evaluate the influence of chemical and physical attributes on the sorption and desorption of tembotrione, as well as its metabolite AE 1417268, on seven soils from different regions of Brazil. The coefficients referring to sorption and desorption, as well as the hysteresis index (Kf, 1/n and H) of tembotrione and its metabolite were influenced by pH, clay content and organic matter. In soil samples with low levels of clay and organic matter, values of sorption coefficients were reduced as pH increased. The desorption of tembotrione and its metabolite in all soils were low, mainly in the clayey ones and in soils with higher organic matter content. The sorption of tembotrione and its metabolites varies with the attributes of soil, presenting a direct relation with clay and organic matter contents and an inverse one with soil pH. The desorption of tembotrione and its metabolite decreased with the increase in clay and organic matter contents in the evaluated soils.